2018
DOI: 10.1080/03079457.2018.1517938
|View full text |Cite
|
Sign up to set email alerts
|

Avian parvovirus: classification, phylogeny, pathogenesis and diagnosis

Abstract: Poultry parvoviruses identified during the early 1980s are found worldwide in intestines from young birds with enteric disease syndromes as well as healthy birds. The chicken parvovirus (ChPV) and turkey parvovirus (TuPV) belong to the Aveparvovirus genus within the subfamily Parvovirinae. Poultry parvoviruses are small, non-enveloped, single-stranded DNA viruses consisting of three open reading frames, the first two encoding the non-structural protein (NS) and nuclear phosphoprotein (NP) and the third encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 63 publications
3
45
0
2
Order By: Relevance
“…Although the observed mortalities for affected farms were not so high, the production performance of ducks that survived the infection was significantly reduced due to growth retardation [ 31 ]. Certain characteristics which justified the difference between NGPV and classical GPV were lower mortalities, resistance of mule and pekin ducks to GPV and the absence of pathological lesions in brain and kidneys in NGPV [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed mortalities for affected farms were not so high, the production performance of ducks that survived the infection was significantly reduced due to growth retardation [ 31 ]. Certain characteristics which justified the difference between NGPV and classical GPV were lower mortalities, resistance of mule and pekin ducks to GPV and the absence of pathological lesions in brain and kidneys in NGPV [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parvoviruses are small, non-enveloped, linear single-stranded DNA viruses [1]. Parvoviruses may have appeared millions of years ago, infecting invertebrates and vertebrates [2]. All parvoviruses that infect vertebrates belong to the parvovirinae subfamily [3].…”
Section: Introductionmentioning
confidence: 99%
“…All parvoviruses that infect vertebrates belong to the parvovirinae subfamily [3]. Parvoviruses are widespread in birds; parvoviruses that cause harm to the health of avians mainly include goose parvovirus (GPV), Muscovy duck parvovirus (MDPV), and chicken and turkey parvoviruses [2]. Recent studies have shown that the diversity of known parvovirus species has greatly expanded and the host range of parvovirus may include the entire animal kingdom [4].…”
Section: Introductionmentioning
confidence: 99%
“…PPV is a non-encapsulated autonomously replicating virus that belongs to the family Parvovirdae, subfamily Parvovirina, and genus Parvovirus [18]. The same genus also includes parvoviruses of cattle, cats, dogs, geese, mice, rats, tigers, rabbits, minks, chickens and raccoons [19][20][21][22][23][24]. The PPV genome is a single and negative-stranded DNA with a full length of about 5000 bp, which contains two open reading frames (ORFs) and covers the entire genome [23,25].…”
mentioning
confidence: 99%